2007
DOI: 10.1074/jbc.m611407200
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM2-Tetraspanin CD82 Complex Inhibits Met and Its Cross-talk with Integrins, Providing a Basis for Control of Cell Motility through Glycosynapse

Abstract: Glycosphingolipids (GSLs) at the cell surface membrane are associated or complexed with signal transducers (Src family kinases and small G-proteins), tetraspanins, growth factor receptors, and integrins. Such organizational framework, defining GSL-modulated or -dependent cell adhesion, motility, and growth, is termed "glycosynapse" (Hakomori, S., and Handa, K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
132
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 54 publications
2
132
0
1
Order By: Relevance
“…G D1a inhibits HGF-induced motility and scattering of cancer cells through suppression of tyrosine phosphorylation of c-Met (33). G M3 and G M2 form heterodimers that specifically interact with tetraspanin (CD82) in glycosynapses, and such complexes inhibit c-Met activation and integrin cross talk (34,35). However, to our knowledge, it is the first demonstration of ganglioside-induced c-Met constitutive activation in cancer cells.…”
Section: Discussionmentioning
confidence: 81%
“…G D1a inhibits HGF-induced motility and scattering of cancer cells through suppression of tyrosine phosphorylation of c-Met (33). G M3 and G M2 form heterodimers that specifically interact with tetraspanin (CD82) in glycosynapses, and such complexes inhibit c-Met activation and integrin cross talk (34,35). However, to our knowledge, it is the first demonstration of ganglioside-induced c-Met constitutive activation in cancer cells.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast to these previous studies, focused on GM3-CD9 interaction that inhibits tumor cell motility, our recent studies (9) addressed the functional role of the GM2/CD82 complex that inhibits (i) hepatocyte growth factor (HGF)-induced cMet tyrosine kinase and (ii) laminin-5-mediated activation of ␣3 and its cross-talk with cMet tyrosine kinase, leading to inhibition of cell motility and growth.…”
mentioning
confidence: 75%
“…Thus, various cell adhesion processes mediated by GSLs and TSP cause extensive phenotypic changes, including reversion from malignant to normal cell phenotype (8,9,25). In analogy, Bissell and colleagues (26,27) showed that functional antibodies directed to ␤1 integrin of breast cancer cells caused reversion, in vitro and in vivo, to normal cellular organization, indicating that malignancy may arise from disorganization of glycosynaptic microdomain rather than from changes in gene structure and expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activities of phospholipase C␥-1 and a variety of Src kinases can be similarly demonstrated to be dramatically affected by genetic or pharmacologic manipulations of cellular glycosphingolipids (9,10). Recently, it has been reported that these changes may be mediated by the direct binding of tetraspanins to membrane glycosphingolipids as part of a larger structure termed a glycosynapse (23). These observations beg an important question, namely, do specific glycosphingolipids and changes in their relative concentrations regulate specific signaling phenomena?…”
Section: Discussionmentioning
confidence: 98%